Customer experience and engagement in the South African retail sector - Munsamy, Nadine (University of the Witwatersrand, Johannesburg, 2022)
Context The aim of this study was to conceptualise and validate a customer experience framework within the South African retail industry. A considerable amount of literature has focused on conversion rather than long-term loyalty and engagement outcomes. The South African retail industry is a mature one in which increasing competition and empowered customers require firms to create sustainable competitive advantage. The shift in power to consumers may be a potential threat or opportunity to firms, making it important to understand customer engagement. In light of this, this study endeavoured to understand the customer experience holistically, from the customers’ perspective, and its effect on the customer perceived value-customer satisfaction-customer loyalty model and how this may affect customer engagement. • A brief statement of the problem Customer experience is not clear in its conceptualisation. Studies that have been undertaken are primarily in the service environment. Customers’ experiences in their decision-making journeys within the purchase funnel are a key component of their experience of the organisation. Technology is reducing both consumer decision-making journeys as well as the loyalty funnel, giving firms fewer opportunities to engender loyalty. Producing a superior value proposition to acquire and retain customers is an important goal for marketing practitioners. In order to do this, they need a clearer understanding of customer journeys. • The method of the data collection A total of 792 respondents participated in the data collection process. The sample was collected from the University of the Witwatersrand database of students. Confirmatory factor analysis was used to check the efficacy of the data, and multiple regression analysis was then conducted. • The key findings The study validates that there is a strong positive effect of customer experience on customer perceived value-customer satisfaction-customer loyalty. Online customer experience has a greater effect on customer perceived value than offline customer experience. The study also validates the causality of the relationships within the South African retail context. There is a strong positive relationship between customer perceived value and customer satisfaction, validating that these are separate constructs. The final hypothesis proposes that customer loyalty may have a positive effect on customer engagement, but the results show a negative and inverse relationship between these constructs. • The key message The results of this study further strengthen the exigency for further conceptualisation and validation of customer experience frameworks in order to manage customer experiences optimally. The results also show that the combined effect of customer experiences in both the online and offline realms is important as these experiences have a strong positive effect on loyalty outcomes, thus validating the importance of the evolution of retail within this context into an omnichannel. Further research needs to be undertaken to assess the effect of customer experience on customer engagement, as this is increasingly becoming an essential element of customer acquisition goals for firms. Results of this study reinforce the importance of the assessment of customer perceived value as a concept separate from customer satisfaction, as literature has called for a holistic framework in which customer experience and customer perceived value may be evaluated.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management (MMSM), Johannesburg, 2022
Keywords: Customer experience; South African retail sector; Retail; UCTD; SDG-8: Decent work and economic growth